Analisis Reputasi Brand, E-Service Quality, dan Electronic Word of Mouth Terhadap Minat Beli Konsumen Tokopedia di Sidoarjo - Surya Farhan Permadi; Lilik Indayani; Muhammad Yani (Permana : Jurnal Perpajakan, Manajemen, dan Akuntansi, 2025)
Advances in information technology have encouraged companies to utilize digital platforms to reach consumers more effectively, including in marketing activities. This study aims to analyze the influence of Brand Reputation, E-Service Quality, and Electronic Word of Mouth (e-WOM) on consumer purchase intent for Tokopedia in Sidoarjo. The approach used is quantitative, with data collected through questionnaires and analyzed using inferential statistical methods. The results of the study indicate that all three independent variables significantly influence consumer purchase intent. Brand Reputation builds trust, E-Service Quality enhances convenience, and e-WOM strengthens purchasing decisions. These findings underscore the importance of consumers' perceptions of brand image, service quality, and digital reviews in driving the success of e-commerce marketing strategies.